Analysis of Coalbed Methane Reservoir Properties Based on Grey Correlation Prediction. Issue 1 (February 2020) - Wu, Jianjun; Meng, Lingpeng; Li, Bing; Chen, Xiaoya; Lu, Han
Abstract: According to the grey system theory, this paper selects some logging parameters that are sensitive to the fluid properties of coalbed methane reservoirs, predicts the fluid properties of unknown coalbed methane reservoirs by using grey correlation analysis method, determines the correlation factor and correlation degree between the evaluation index of fluid properties of coalbed methane reservoirs and actual data, and quantitatively describes the categories of unknown fluid properties according to the correlation degree. By analyzing various logging data and comparing the identification result with the gas test conclusion, the accuracy rate is as high as 95%, which can accurately judge the gas-bearing property of the reservoir. This shows that the grey correlation prediction is feasible, with high accuracy and ideal effect.